Mental Health Literacy among Mothers of Secondary Level Students: A Cross-Sectional Study in Urban Nepal - Neupane, Anuka Limbu (Journal of Multidisciplinary Research Advancements, 2026)
Mental health literacy (MHL) among mothers is vital for early detection and management of mental health issues among adolescents but has been inadequately explored in urban Nepal. This study evaluated MHL among mothers of secondary school-going children in Sanepa, Lalitpur. A cross-sectional survey was carried out among 222 mothers of eight schools in Sanepa, Lalitpur, using the standardized Mental Health Literacy Questionnaire (MHLq). Non-parametric tests were used to explore the correlation between MHL and sociodemographic factors. The majority of mothers showed high levels of MHL (87.8%), especially in self-help methods (90.5% had high levels) and knowledge (79.3% had high levels). However, 85.1% of mothers knew that they did not know anyone with mental health issues. There were significant caste-related inequalities (p=.035), with lower scores in marginalized castes. There was weak negative correlation between age and MHL (r=-0.206) and mild differences related to employment. Despite high literacy levels, there are important experiential gaps in awareness, recognition of serious mental illness, and caste-related disparities. Culturally adapted family-based interventions are urgently required.